REFLECTIONS OF ISLAMIC THINKERS ON THE ONTOLOGY OF THE SOUL AND ITS RELATIONS IN THE QURAN - Taswin, Mubarak (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
This article examines the ontology of the soul as perceived by three Islamic philosophers: al-Kindi, al-Farrabi, and Ibn Sina, who later put forward some of the ideas of Imam al-Ghazali afterwards. At the level of understanding of these three figures, they agree that the soul is eternal. Still, al-Kindi views a soul that does not reach perfection. It wanders from one dimension to another until it comes to self-purification and is worthy of entering the realm of truth, in the case of al-Farrabi, who will destroy the soul this soul along with the destruction of the body, because it is bound to matter. As for Ibn Sina, it is more likely that who will curse the soul will be condemned. Similarly, Imam al-Ghazali is more directed to the soul, which has three levels, the lowest is the vegetable soul than, the organic soul, and the highest is the rational soul. This view bears a resemblance to the three previous figures. It's just that Imam al-Ghazali was not too clear in declaring the death of the soul. Finally, this article examines mental conflicts by bringing up the western figure Sigmund Freud by realizing this idea with the idea of ​​the condition of the soul in the Koran.